IMPROVING TEACHER DISCIPLINE IN IMPLEMENTING LEARNING THROUGH THE EXAMPLE OF THE SCHOOL PRINCPAL - Norpah, Norpah (JURNAL SOCIUS, 2024)
This School Action Research was carried out because of the low level of teacher discipline in carrying out daily learning. Therefore, this research aims to improve teacher discipline in carrying out learning through the example of the school principal. The research was carried out in two cycles for eight weeks. Data collection through observation and discussion using observation sheets during action and teacher coaching books. The research results showed that teacher discipline in carrying out learning increased on average overall from 87% in cycle I to 88% in cycle II. In this way, the principal's example can improve teacher discipline in implementing learning at SMPN 7 Muara Uya in 2020